Production of Polyhydroxyalkanoates by Two Halophilic Archaeal Isolates from Chott El Jerid Using Inexpensive Carbon Sources - Manel Ben Abdallah; Fatma Karray; Sami Sayadi (Biomolecules, 2020)
The large use of conventional plastics has resulted in serious environmental problems. Polyhydroxyalkanoates represent a potent replacement to synthetic plastics because of their biodegradable nature. This study aimed to screen bacteria and archaea isolated from an extreme environment, the salt lake Chott El Jerid for the accumulation of these inclusions. Among them, two archaeal strains showed positive results with phenotypic and genotypic methods. Phylogenetic analysis, based on the 16S rRNA gene, indicated that polyhydroxyalkanoate (PHA)-producing archaeal isolates CEJGTEA101 and CEJEA36 were related to Natrinema altunense and Haloterrigena jeotgali, respectively. Gas chromatography and UV-visible spectrophotometric analyses revealed that the PHA were identified as polyhydroxybutyrate and polyhydroxyvalerate, respectively. According to gas chromatography analysis, the strain CEJGTEA101 produced maximum yield of 7 wt % at 37 °C; pH 6.5; 20% NaCl and the strain CEJEA36 produced 3.6 wt % at 37 °C; pH 7; 25% NaCl in a medium supplemented with 2% glucose. Under nutritionally optimal cultivation conditions, polymers were extracted from these strains and were determined by gravimetric analysis yielding PHA production of 35% and 25% of cell dry weight. In conclusion, optimization of PHA production from inexpensive industrial wastes and carbon sources has considerable interest for reducing costs and obtaining high yield.